ℋ2 and ℋ∞ analysis and state feedback control design for discrete-time constrained switched linear systems. Issue 10 (3rd October 2021) - Falchetto, Vinícius B.; Souza, Matheus; Fioravanti, André R.; Shorten, Robert N.
Abstract: This paper presents the stability and performance conditions for discrete-time constrained switched linear systems under arbitrary switching. Design methods for such systems, which constrain the set of admissible switching sequences to attain stability and a desired performance level, are also presented. The key procedures presented in this paper are based on classic convex optimisation and graph theory results. Simulations and numerical examples are included to illustrate the main features of the developed theory.